An Optimized Process for the Preparation of Aqueous Ferric Carboxymaltose: Synthesis and Structural Characterization - Tabasi, Ozra; Razlighi, Mahdi R.; Darbandi, Mohammad Ali (Pharmaceutical Nanotechnology, 2021)
Background: Ferric carboxymaltose (FCM) formulation consists of iron-carbohydrate nanoparticles where iron-oxyhydroxide as a core is covered by a carbohydrate shell. The present work provides an improved synthesis process of FCM as an intravenous iron, active pharmaceutical ingredient. Methods: Water-soluble FCM complex was prepared from the reaction of ferric hydroxide precipitation with an aqueous solution of oxidized maltodextrin (MD) at optimum temperature and pH conditions. A systematic approach was followed to obtain the optimal weight ratio of the maltodextrin/ ferric chloride for FCM synthesis process with suitable-sized nanoparticles. Physical characterization of newly synthesized ferric carboxymaltose (FCM-NP) was performed to establish its equivalency with the reference product (Ferinject). Results: The size distribution of the whole nanoparticles determined by dynamic light scattering (DLS) was in the range of 15-40 nm with an average particle size of 26 ± 6.6 and 25.8 ± 4.9 for FCM-NP and Ferinject, respectively. X-ray diffraction (XRD) results of FCM-NP and Ferinject indicated the Akaganeite structure of iron-oxyhydroxide. The iron content of particles (cores) measured by Atomic absorption spectroscopy (AAS) was almost equal for the two formulations. The Fourier transform infrared (FTIR) spectra of Ferinject and FCM-NP were approximately similar. Conclusion: Various analytical methods, including FTIR spectroscopy, XRD analysis, DLS technique, TEM, and AAS were employed. It was observed that the specifications of FCM-NP obtained by these analyses were almost identical to those of Ferinject. Accordingly, the two formulations were considered comparable.
Keywords: carbohydrate